TINJAUAN TENTANG KAIDAH HUKUM DAN KAIDAH-KAIDAH BUKAN HUKUM DALAM KEHIDUPAN MANUSIA: Array - Cecep Cahya Supena (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Every human being in living his life always has various kinds of needs and interests. To be able to fulfill the needs and interests of their lives, sometimes humans collaborate with each other, but sometimes they also clash with each other. To avoid these dangerous clashes, human life needs to be regulated and controlled in order to create security, order and justice. Such regulation and control is carried out through the application of principles. The existence of rules for human life is absolutely necessary, because they can serve as guidance or guidance for humans in living their personal, social, national and state lives. Not only citizens must comply with these principles, but the state (government) in exercising its power must comply with these principles, so that there will be no arbitrariness (absolute or authoritarian) in exercising its power.